UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN KIMIA MELALUI METODE CURAH PENDAPAT (BRAINSTORMING) PADA SISWA KELAS XI IPA 3 SMAN 1 TALAMAU - Mairisna, Mairisna (Jurnal Manajemen Pendidikan, 2017)
Based on the results of student learning Class XI IPA 3 SMAN 1 Talamau in sub Chemistry Subjects Determine the type of salt that has hydrolysis in water and measure and calculate the pH Salt solution found that the student learning outcomes in sub subject chemistry Determining the type of salt that hydrolysis in water As well as measuring and calculating pH The salt solution is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in sub subject chemistry Determine the type of salt that has hydrolysis in water and measure and calculate the pH Salt solution through Brainstorming Method in Class XI IPA 3 SMAN 1 Talamau Kabupaten Pasaman Barat. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 26 students of Class XI IPA 3 SMAN 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that Brainstorming Method can improve student learning outcomes in sub subject chemistry Determine the type of salt that has hydrolysis in water and measure and calculate the pH of the salt solution at SMAN 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 57.85 (Enough) increased to 84.77 (good) with an increase of 26.92%.